Spatial and temporal concentration of tourism demand in northern Portugal: regional policy recommendations to promote tourism competition and portofolio diversity - Fernandes, Paula O. (2020)
The northern region of Portugal, in the last years, has experienced a growing number of visitors from different countries, which may indicate the emergence of an overtourism phenomenon in some particular municipalities or specific spaces. This phenomenon may cause significant destruction of the living conditions of residents, landscapes, seascapes, air and water quality, causing economic inequalities and social exclusion. The concentration of tourism activity in different municipality regions can be measured with a well know concentration measured, the Herfindahl-Hirschman Index. Using as variables the number and nationality of visitors and their expenditures it is possible to follow the concentration of tourism visitors and expenditure, all over the 8 NUTIII regions located in the Northen of Portugal, and describe the routes of distribution of the tourism indicators from urban to rural areas following a more nature-oriented tourism. The results serve as a dipping compass for more oriented and well-targeted tourism policies.